2018
DOI: 10.1002/msc.1361
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the experiences of rheumatology nurses counselling patients on methotrexate therapy

Abstract: Participants reported that the majority of the consultation focused on conveying information, with little opportunity for patient interaction and questions. We suggest that there is a clear need for further exploration of these consultations, to identify possible training needs. Participants also used standard written information to guide both the structure and content of the consultation limiting patients'; opportunities to ask questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The education and training of nurses were also studied as this is an important topic for ensuring that patients receive the best possible care (Robinson, 2021;Robinson et al, 2017Robinson et al, , 2018Vlieland et al, 2016). A study conducted in the UK found that most nurses lacked knowledge and confidence in managing patients taking MTX (Robinson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The education and training of nurses were also studied as this is an important topic for ensuring that patients receive the best possible care (Robinson, 2021;Robinson et al, 2017Robinson et al, , 2018Vlieland et al, 2016). A study conducted in the UK found that most nurses lacked knowledge and confidence in managing patients taking MTX (Robinson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another concern reported by nurses is that most consultations focus on transmitting information with little opportunity for interaction and clarification of patient doubts (Robinson, 2021). Using standardised written information to guide the consultation's structure and content is also seen as helpful (Robinson et al., 2018). Some educational guides and booklets have been developed in the UK (Martin et al., 2019; Royal College of Nursing, 2019; Sowden et al., 2012; The Medicines Management Team for NHS Eastern Cheshire CCG, 2021), and although relevant, they might not be easily transferred and applied to other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Confidence in educating patients on methotrexate was associated with gaining experience in delivering the consultation rather than informed by patient evaluation. A subsequent interview study of nurses suggested that during the consultation process, nurses focused mainly on giving information, which led to little opportunity for interaction and patient led discussion (Robinson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%